Unsur Kesenian dalam Novel Sirkus Pohon Karya Andrea Hirata: Kajian Antropologi Sastra - Enny Hidajati; Andi Burka (LP4MK STKIP PGRI Lubuklinggau, 2020)
One of the novels that are of interest to readers is because they contain the cultural culture of a society. For this reason, the importance of the study of the artistic elements contained in the novel. The purpose of this study was to describe the artistic elements contained in the Sirkus Pohon novel by Andrea Hirata. The data in this study are the Sirkus Pohon novel by Andrea Hirata. The research method uses the method of literary anthropology. Data collection techniques using documentation techniques by reading and recording research data. Test the validity of the data using member check and validation of literary anthropologists. Data analysis techniques are by analyzing quotations containing art, connecting the findings of art with the culture that exists in the text, and interpreting art culture contextually. The results showed that in the Sirkus Pohon novel by Andrea Hirata contains variations of artistic elements, namely drama (theater), literary arts, painting, drawing art, interior design, architectural design, and kria art. All elements of the art are displayed and add insight into the culture of the Belitung community.